Finite Element Analysis of Phosphate Movement through a Clayey-Sandy Soil by using Geo-Slope Software (CTRAN/W) - Arshad, Imran; Vallejera, Clea Anne E.; Khan, Zaheer Ahmed (PSM Biological Research, 2018)
A hypothetical 2-D numerical model of a clayey-sandy soil profile had been developed by using Geo-Slope software to analyze the water flow (SEEP/W) and phosphate movement (CTRAN/W) through the sub-surface region of the soil. Results showed that streamlines and equipotential lines are normal to each other and vectors displaying the velocity of the flow direction have the average flow rate of 1.2067 x 10-5 ft3/sec/ft (0.000342 LPS). The Advection-Dispersion Analysis revealed that the adsorption of phosphate on the soil particles is linearly related to the concentration which was represented as contours with different colors. The phosphate concentration after 365 days was 0.93 gm/ft3 at the toe point of the drain. The overall average velocity for the selected nodal points at head, middle and tail sections were 0.2262, 0.3997, and 0.6834 ft/day, respectively. Only the nodal points present at the tail section reached the free exit drain in between 300-365 days with an average velocity of 0.6855 ft/day. The particles present at the head and middle sections of the land were moving slowly as compared to the tail section. However, results may vary for the other types and texture of soils.